The Relationship between Team Communication and Team Performance among Selected Banks’ Employees in Selangor - Fauzana Nawari; Nor Hazana Abdullah (Research in Management of Technology and Business, 2024)
Team performance refers to the ability of a group of individuals to work together cohesively and efficiently towards a common goal. One of the issues that can arise and impact team performance in an organization is poor communication. Effective communication is crucial for team performance to avoid misunderstandings, delays, and mistakes. Hence, the purpose of this research is to identify the level of team communication and team performance among selected banks’ employees in Selangor. It also aims to investigate the relationship between team communication and team performance. This research employed quantitative approach using structured questionnaire to collect data. A total of 400 employees from four selected banks which are Maybank, CIMB, RHB and Bank Islam were chosen via quota sampling in this research. The questionnaires by Lurie et al. (2011) and Palacios et al. (2016) were used to measure team communication and team performance levels respectively. The collected data was then analysed using IBM Statistical Package for Social Science (SPSS). It was found that team communication and team performance were both at high levels. Moreover, team communication is positively correlated to team performance among selected banks’ employees in Selangor. This research strengthened the notion of the importance of team communication for team performance enhancement and improvement.